Policy Reforms Affecting Agricultural Incentives - Anderson, Kym (World Bank, 2012)
For decades, earnings from farming in many developing countries have been depressed by a pro-urban bias in own-country policies, as well as by governments of richer countries favoring their farmers with import barriers and subsidies. Both sets of policies reduce national and global economic welfare and inhibit agricultural trade and economic growth. They almost certainly add to inequality and poverty in developing countries, since three-quarters of the world's billion poorest people depend on farming for their livelihood. During the past two decades, however, numerous developing country governments have reduced their sectoral and trade policy distortions, while some high-income countries also have begun reducing market-distorting aspects of their farm policies. The author surveys the changing extent of policy distortions to prices faced by developing-country farmers over the past half century, and provides a summary of new empirical estimates from a global economy-wide model that yield estimates of how much could be gained by removing the interventions remaining as of 2004. The author concludes by pointing to the scope and prospects for further pro-poor policy reform in both developing and high-income countries.